2010
DOI: 10.1007/s12601-010-0020-5
|View full text |Cite
|
Sign up to set email alerts
|

Meiobenthos assemblages in the mekong estuarine system with special focus on free-living marine nematodes

Abstract: Meiobenthos assemblages in eight estuaries of the Mekong river system were investigated in August 2008 (from the Cua Tieu estuary to the Tran De estuary). In each estuary, one sampling station was established for meiobenthos sampling. Twelve major taxa of meiobenthos were recorded in this estuarine system, including Nematoda, and Crustacean Nauplii larvae. The densities of the meiobenthos range from 581 to 3168 inds/10 cm 2 . Nematodes always occupy the highest numbers with a percentage ranging from 64-99%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
4
2
Order By: Relevance
“…The dominant families of this study are little similar compared with the study by Adão et al (2008) [1] because of two dominant families Comesomatidae and Desmodoridae were not recorded in Ham Luong and Cung Hau estuaries while at the Mondego and the Mira estuaries the authors found the nematode dominant families were Comesomatidae,Desmodoridae, Chromadoridae and Xyalidae. This result is also quite similar with the recent study byQuang et al (2010) [29] on the marine stations at the mouth of eight estuaries of the Me Kong delta. The authors recorded the family Xyalidae as the most important family in the nematode communities, followed by the Desmodoridae, Monhysteridae and Chromadoridae.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The dominant families of this study are little similar compared with the study by Adão et al (2008) [1] because of two dominant families Comesomatidae and Desmodoridae were not recorded in Ham Luong and Cung Hau estuaries while at the Mondego and the Mira estuaries the authors found the nematode dominant families were Comesomatidae,Desmodoridae, Chromadoridae and Xyalidae. This result is also quite similar with the recent study byQuang et al (2010) [29] on the marine stations at the mouth of eight estuaries of the Me Kong delta. The authors recorded the family Xyalidae as the most important family in the nematode communities, followed by the Desmodoridae, Monhysteridae and Chromadoridae.…”
supporting
confidence: 93%
“…In Ham Luong, the mean nematode density varied between 90 ± 31 inds/10 cm² (EHL2) and 1524 ± 269 inds/10cm² (EHL4) on the average, while in Cung Hau, the mean nematode density was varying between 105 ± 79 inds/10 cm² (ECH2) station and 1120 ± 534 inds/10 cm² at station ECH1 ( Figure 2). This result is much lower compared with the recent study by Quang et al (2010) [29], where nematode density ranged from 454.0 ± 289.9 to 3137.7 ± 337.1 inds/10 cm². However at the same two stations in the mouth of Ham Luong and Cung Hau, the author recorded nematode densities in the rainy season of 454 ± 290 inds/10 cm² at ECH1 and 683.7 ± 374.4 inds/10 cm² at EHL1.…”
Section: Nematode Density Abundance and Compositioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Food sources such as bacteria or microalgae were abundant in mudflat sediment, and Daptonema which has been characterized as 1B (non-selective feeder) mostly consumed bacteria and microalgae. Heip et al (1985) states that several nematode genera common in many estuarine ecosystems were Adoncholaimus, Anoplostoma, Axonolaimus, Daptonema, Leptolaimus, Microlaimus, Monhystera, Metachromadora, Ptycholaimellus, Sabatieria, Theristus, Tripyloides, and Viscosia. In a different study, Quang et al (2010) found other genera that were also present in high abundance in the Mekong estuarine ecosystem, i.e., Halalaimus, Rhynchonema, Parodontophora, Terschellingia, Desmodora, Onyx, Leptolaimoides, Oncholaimellus, Omicronema, Rhinema, and Haliplectus. However, in our study, Spilophorella, Onyx, Rhynchonema, Viscosia, and Paredesmodora were present in high abundance (Figure 2) in the estuarine ecosystem.…”
Section: R E S U L T S a N D Discussion Smentioning
confidence: 92%